Sustainable Bee-keeping through Farmers FIRST Project interventions in Nainital district of Uttarakhand - Kashyap, S K; Kholiya, Monika (Indian Farming, 2022)
There is enormous potential for bee-keeping in the country. However, due to lack of improved standardized equipments and scientific knowledge, bee-keeping is not being practiced by the bee-keepers serving as one of the major reasons behind low production of honey. In Uttarakhand, farmers use traditional practices for bee-keeping which gives them less economic benefits. In order to obtain high output from bee-keeping, it is necessary for the bee-keepers to use modern technologies and scientific knowledge, participate in the training and other capacity building programmes. As per the objective, Farmers FIRST Project transferred the improved technologies among the bee-keeping farmers in Jeoli village, trained them to use scientific methods of bee-keeping and made them capable to use honey processing unit and other related equipments which eventually led to alleviate their income and standard of living. Seeing the benefits of bee-keepers, other farmers in the village also have taken up beekeeping as an enterprise to generate additional income. This intervention has helped the bee-keepers to lead sustainable bee-keeping in Jeoli village of Uttarakhand state.